Literature Study of STAD Type Cooperative Learning Model to Improve Student's Mathematical Communication Skills - Pratama, Rizky Putra (JMEA : Journal of Mathematics Education and Application, 2025)
This research is the result of literature research as a technique used to study several references to books and the results of similar research previously conducted by others according to the problem being studied. This study uses a descriptive research method through a qualitative approach. This study aims to determine the improvement of students' mathematical communication skills by applying the STAD Type Cooperative learning model and analyze the causative factors. The data of this study was obtained from several journals and articles that revealed the improvement of students' mathematical communication skills with the application of the STAD Type Cooperative learning model. The researcher's findings show that from the indicators of mathematical communication and syntax of the STAD Type Cooperative learning model, each journal and article studied with the one written by the researcher has several similarities in indicators that explain that there is a suitability of the learning model to improve students' mathematical communication skills. For the results of each journal and article studied, it was stated that there was an increase in student learning outcomes from the students' mathematical communication skills. The STAD Type Cooperative learning model is also considered effective in improving students' mathematical communication skills. From all the articles and journals that were researched experienced an increase in grades and good learning achievement results, it can be concluded that the application of the STAD Type Cooperative learning model can improve students' mathematical communication skills.